A Complete Network-On-Chip Emulation Framework - Genko, N.; Atienza, D.; Micheli, G. De; Mendias, J. M.; Hermida, R.; Catthoor, F. (Design, Automation and Test in Europe, 2005)
Current Systems-On-Chip (SoC) execute applications that demand extensive parallel processing. Networks-On-Chip (NoC) provide a structured way of realizing interconnections on silicon, and obviate the limitations of bus-based solution. NoCs can have regular or ad hoc topologies, and functional validation is essential to assess their correctness and performance. In this paper, we present a flexible emulation environment implemented on an FPGA that is suitable to explore, evaluate and compare a wide range of NoC solutions with a very limited effort. Our experimental results show a speed-up of four orders of magnitude with respect to cycle-accurate HDL simulation, while retaining cycle accuracy. With our emulation framework, designers can explore and optimize a various range of solutions, as well as characterize quickly performance figures.